EXTENT OF AVAILABILITY AND UTILIZATION OF INFORMATION AND COMMUNICATION TECHNOLOGY RESOURCES IN BUSINESS EDUCATION PROGRAMME OF COLLEGES OF EDUCATION IN DELTA STATE (NAU Journal of Technology and Vocational Education, 2024)
The study examined the extent of availability and utilization of information andcommunication technology resources in business teacher education programme ofcolleges of education in Delta State, Nigeria. Two research questions guided thestudy and two null hypotheses were tested at 0.05 level of significance. The studyadopted descriptive survey design. The entire population of 114 business educationlecturers in all the four colleges of education in Delta State was used for the studywithout sampling. Data was collected for the study through direct observation bythe researcher using NCCE benchmark and administration of a validatedquestionnaire on the respondents. The reliability of the questionnaire wasestablished using Cronbach Alpha formula which yielded a reliability coefficient of0.801. Frequency count and simple percentage were used to answer researchquestion one and mean and standard deviation were used to answer researchquestion two. t-test statistic was used to test the hypotheses at 0.05 level ofsignificance. The findings of the study revealed that ICT resourcesas stipulated bythe benchmark of NCCE for business education programmes were not available incolleges of education in Delta State. Business educators’ rarely utilized ICTresources in business teacher education programmes in colleges of education inDelta State. The study further disclosed that business educators in colleges ofeducation did not differ significantly in their mean ratings on the extent ofutilization of ICT resources in business education programmes based oninstitutional ownership and location. The study concluded that the inadequacy andlow level of utilization of ICT resources by business educators will negativelyaffected the technological competencies of business education students to succeedand curve a niche of their own in the digitalized business world. It wasrecommended among others that management of colleges of education should enter into partnership with ICT manufacturing organizations to assist in improvingthe supply of ICT resources in business education programme. This is to enhancebusiness education students’ academic performance and boost the qualityassurance indices of the programme.
Keywords: Information communication technology Resources, business education, business educators, availability and utilization